2003
DOI: 10.1111/j.1469-8749.2003.tb00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Adults with cerebral palsy: walking ability after progressive strength training

Abstract: The purpose of this study was to evaluate effects of a progressive strength training programme on walking ability in adults with cerebral palsy. Ten individuals with spastic diplegia (seven males, three females; mean age 31, range 23–44 years) participated twice a week over 10 weeks. Seven individuals with spastic diplegia (four males, three females; mean age 33, range 25–47 years) who did not receive strength training served as controls. All individuals were ambulatory but motor ability ranged from functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
86
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 39 publications
7
86
1
4
Order By: Relevance
“…A recent systematic review provided an overview of the measurement properties of WTs used within this field and concluded that the 6-min WT was the most extensively researched, best tolerated and most reflective of activities of daily living [2]. Despite the growing use of WTs as a useful outcome tool within areas of rehabilitation medicine [3][4][5][6], research regards their validity and reliability in children and adults with disability is just starting to appear within the literature. Three recent papers concluded high test-retest reliability of the 6-min protocol in adults [7] and children [8,9] with cerebral palsy (CP), although results conflicted with regards to the necessity of a practice walk.…”
mentioning
confidence: 99%
“…A recent systematic review provided an overview of the measurement properties of WTs used within this field and concluded that the 6-min WT was the most extensively researched, best tolerated and most reflective of activities of daily living [2]. Despite the growing use of WTs as a useful outcome tool within areas of rehabilitation medicine [3][4][5][6], research regards their validity and reliability in children and adults with disability is just starting to appear within the literature. Three recent papers concluded high test-retest reliability of the 6-min protocol in adults [7] and children [8,9] with cerebral palsy (CP), although results conflicted with regards to the necessity of a practice walk.…”
mentioning
confidence: 99%
“…[12][13][14][15][16] Most of these previous studies, however, involved ambulant young children with CP using routine exercise methods such as weightlifting and circuit training. Older young people who are non-ambulant do not have the physical ability to perform routine exercises but they may be able to pedal independently when supported on a static exercise bicycle.…”
mentioning
confidence: 99%
“…Strength training effect Although strength training was initially contraindicated because it was believed to stiffen muscles, resulting in an increase in spasticity and a decrease in range of motion (Bobath, 1971), current scientific evidence dictates the contrary (Andersson, Grooten, Hellsten, Kaping & Mattsson, 2003;Damiano, 2006;Dodd, Taylor & Damiano, 2002;Engsberg, Ross & Collins, 2006;MacPhail & Kramer, 1995). In the last decade, the strength training as part of the physical therapy has become more frequent due to the positive results of different studies (Andersson et al, 2003;Blundell, Sheperd, Dean, Adams & Cahill, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they also provided evidence which indicated that muscle spasticity was not deteriorated as a result of strength training in adults with CP (Andersson et al, 2003). Blundell et al (2003) carried out a training program with children with CP that consisted of a physical circuit composed of tasks such as treadmill walking, step-ups, sit-to-stands and leg presses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation